Recent Advances in Geotechnical Post-earthquake Reconnaissance - Jonathan D. Bray; James D. Frost; Ellen M. Rathje; Fernando E. Garcia (Frontiers in Built Environment, 2019)
Field observations are particularly important in geotechnical engineering, because it is difficult to replicate in the laboratory the response of soil deposits built by nature over thousands of years. Detailed mapping of damaged and undamaged areas provides the data for the well-documented case histories that drive the development of many current design procedures. Thus, documenting key insights from earthquakes advance research and practice. This has been a primary goal of the National Science Foundation-sponsored Geotechnical Extreme Events Reconnaissance (GEER) Association since its inception almost 20 years ago. New technologies are continually employed by GEER teams to capture ground deformation and its effects. These technologies include Light Imaging Detection and Ranging (LIDAR) and Structure-from-Motion (SfM) image processing techniques for generating and visualizing three-dimensional point cloud data sets. New sensor deployment platforms such as Unmanned Aerial Vehicles (UAVs) are playing an integral role in the data collection process. Unanticipated observations from major events often catalyze new research directions. An overview of some of these recent integrated technology deployments and their role at the core of earthquake disaster analysis is presented. Important advancements are possible through post-event research if their effects are captured and shared effectively.